2020
DOI: 10.5114/ceji.2019.92492
|View full text |Cite
|
Sign up to set email alerts
|

STAT4 sequence variant and elevated gene expression are associated with type 1 diabetes in Polish children

Abstract: Introduction: type 1 diabetes (t1D) is caused by the autoimmune destruction of pancreatic β cells, resulting from coincident genetic predisposition and some environmental triggers. signal transducer and activator of transcription 4 (stat4) gene encodes a transcription factor, which promotes th1 cell differentiation, interferon γ production, and development of th17 cells. Polymorphisms of stat4 are associated with several autoimmune conditions, while studies in t1d provided inconsistent results. this analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
4
0
1
Order By: Relevance
“…A meta-analysis of the significance of STAT4 rs7574865 T1D risk allele T has confirmed its association with T1D in multiple populations, in addition to the already earlier found association with other autoimmune diseases ( 34 ). A recent study also reported a higher STAT4 expression level in peripheral blood mononuclear cells in T1D cases compared to controls and an association of the rs7574865 T allele with younger age at the T1D diagnosis ( 35 ). The finding of a young age at diagnosis in risk allele positive children concurs with our finding of rs7574865 risk allele T increasing development of AABs and with the association of IAA as the first AAB because IAA dominates over GADA as the first AAB among the youngest seroconverted children, which is also reflected in a younger age at diagnosis ( 36 ).…”
Section: Discussionmentioning
confidence: 91%
“…A meta-analysis of the significance of STAT4 rs7574865 T1D risk allele T has confirmed its association with T1D in multiple populations, in addition to the already earlier found association with other autoimmune diseases ( 34 ). A recent study also reported a higher STAT4 expression level in peripheral blood mononuclear cells in T1D cases compared to controls and an association of the rs7574865 T allele with younger age at the T1D diagnosis ( 35 ). The finding of a young age at diagnosis in risk allele positive children concurs with our finding of rs7574865 risk allele T increasing development of AABs and with the association of IAA as the first AAB because IAA dominates over GADA as the first AAB among the youngest seroconverted children, which is also reflected in a younger age at diagnosis ( 36 ).…”
Section: Discussionmentioning
confidence: 91%
“…Most of the earlier studies on Asian and European populations confirmed that rs7574865 has a role in the incidence of diabetes type 1 [43,44]. Also, a meta-analysis study performed on Caucasians and Asian subjects showed that it was associated with diabetes risk (P < 0.5) [45], and there was a study that confirmed the STAT4 was overexpressed from T1D Polish patients [46]. In contrast, a study among the Korean population, the Tunisian and Brazilian population showed no evidence of the association of the variant and T1D [20,47,48], while our study showed that the rs7574865 (T) allele is accompanied with increased risk for type 1 diabetes among Egyptians, same as another study on Greek patients [49] and Northeastern Chinese Han population [41,44].…”
Section: Discussionmentioning
confidence: 97%
“…In this investigation, we also constructed a miRNA-hub gene regulatory network and TF-hub gene regulatory network for the hub genes. Mirza et al [275], Warshauer et al [276], Fichna et al [277], Zhang et al [278] and Abd-Allah et al [279] reported that the altered expression of the hsa-mir-133a-3p, STAT3, STAT4, SOX2 and VDR (vitamin D receptor) are correlated with T1DM. Recent studies have proposed that the hsa-mir-133a-3p [280], STAT3 [281], STAT4 [282], FOXA2 [283], FOXM1 [284], EGR1 [285], CUX1 [286] and VDR (vitamin D receptor) [287] are associated with obesity.…”
Section: Discussionmentioning
confidence: 99%